Hydrogen production electrode, preparation method thereof and hydrogen production device
By using porous coatings of materials such as lanthanide nickel-based alloy compounds in the hydrogen production electrode, the problems of electrode oxidation inactivation, limited catalytic activity and poor stability in the prior art are solved, and an efficient and stable hydrogen production process is achieved.
Patent Information
- Application Number
- CN202411928548.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing alkaline electrolytic hydrogen production technology, the electrode has problems such as oxidative inactivation, limited catalytic activity, low hydrogen evolution efficiency and poor long-term stability.
A hydrogen-making electrode is provided, including a metal matrix and a porous coating arranged on the surface of the metal matrix, the porous coating consisting of a nickel-based metal, a cobalt-based metal, an iron-based metal and a lanthanide nickel-based alloy compound. The electrodes are formed by specific preparation methods, including mixing, coating and reaction, to form electrodes with high catalytic activity and stability.
This hydrogen-making electrode can effectively suppress the oxidation caused by the cathode due to reverse current, improve catalytic activity and coating stability, and improve hydrogen-making efficiency and electrode life.
Smart Images

Figure CN119710773A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydrogen production, and in particular to a hydrogen production electrode and a preparation method thereof, and a hydrogen production device. Background Art
[0002] Alkaline water electrolysis (AWE) technology has good economic and scalable prospects, but the electrodes in the existing technology still have the following problems:
[0003] 1. Oxidative deactivation: Since the electrolyzer is frequently powered off due to unstable renewable energy supply, the reverse current will cause irreversible oxidation of the cathode to generate β-Ni(OH)2 or NiO phase, thereby reducing the catalytic activity of the electrode;
[0004] 2. Limited catalytic activity and low hydrogen evolution efficiency: Traditional nickel-based catalysts exhibit high hydrogen evolution overpotential at high current density, which affects hydrogen production efficiency;
[0005] 3. Poor long-term stability: Under alkaline conditions, the mechanical stability and anti-peeling ability of the electrode catalytic coating are insufficient, resulting in a shortened electrode life.
[0006] Therefore, there is an urgent need to provide a new hydrogen production electrode to solve the above problems. Summary of the invention
[0007] The purpose of the present application is to provide a hydrogen production electrode and a preparation method thereof and a hydrogen production device to solve the above problems.
[0008] To achieve the above objectives, the present application provides a hydrogen production electrode in a first aspect, comprising a metal substrate and a porous coating disposed on the surface of the metal substrate;
[0009] The porous coating comprises a first metal material and a second metal material;
[0010] The first metal material includes one or more of nickel-based metals, cobalt-based metals, and iron-based metals;
[0011] The second metal material includes a lanthanide nickel-based alloy compound.
[0012] Optionally, the lanthanide nickel-based alloy compound includes LaNi5, La2Ni7, La X Pr 1-X Ni5, La X Ce 1-X One or more of Ni5, MmNi5.
[0013] Optionally, the metal matrix includes one or more of nickel mesh, nickel felt, and nickel foam.
[0014] The second aspect of the present application provides a method for preparing the hydrogen production electrode, comprising:
[0015] The first metal material, the second metal material and the pore-forming agent are first mixed to obtain a coating powder;
[0016] Applying the coating powder to the surface of a metal substrate to obtain a coated substrate;
[0017] The coated substrate and the alkaline solution are mixed for a second time to react to obtain the hydrogen production electrode.
[0018] Optionally, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0019] A. The metal substrate is also roughened before coating;
[0020] B. The mass ratio of the first metal material, the second metal material and the pore-forming agent is 60-80:5-10:15-30.
[0021] Optionally, the sandblasting pressure for the roughening is 0.2MPa-0.5MPa, the sandblasting distance is 50mm-150mm, and the sandblasting angle is 60°-90°.
[0022] Optionally, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0023] A. The coating powder applied during the coating is 240 g / m 2 -300g / m 2 ;
[0024] B. The coating includes one or more of plasma spraying, arc spraying, magnetron sputtering, and electroplating.
[0025] Optionally, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0026] A. The spraying power of the plasma spraying is 20kW-50kW, the spraying distance is 130mm-170mm, and the spraying angle is 60°-90°;
[0027] B. During the plasma spraying process, the argon gas flow rate is 50 L / min-80 L / min, and the hydrogen gas flow rate is 1 L / min-10 L / min.
[0028] Optionally, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0029] A. The reaction temperature is 70°C-90°C and the reaction time is 4h-8h;
[0030] B. The alkaline solution includes KOH solution and / or NaOH solution.
[0031] A third aspect of the present application provides a hydrogen production device, comprising the hydrogen production electrode or a hydrogen production electrode prepared by the hydrogen production electrode preparation method.
[0032] Compared with the prior art, the beneficial effects of this application include:
[0033] The hydrogen production electrode provided by the present application has a first metal material with high electrochemical catalytic activity, but when a reverse current is generated in the hydrogen production electrode, the surface of the first metal material is easily oxidized to form an oxide film, which reduces its catalytic activity. Through the unique role of the second metal material in the porous coating layer in the catalytic coating, when the cathode electrode generates a reverse current, the hydrogen stored in the second metal material is slowly released to prevent the cathode electrode from being oxidized; the oxidation of the cathode in the hydrogen production electrode caused by the reverse current is suppressed, and at the same time, the second metal material has a high electrochemical catalytic activity, which can reduce the hydrogen evolution potential and improve the catalytic activity and coating stability.
[0034] The preparation method of the hydrogen production electrode provided in the present application can be industrially produced on a large scale with low production cost.
[0035] The hydrogen production device provided in the present application has good catalytic performance and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0037] Figure 1 The SEM image of the hydrogen production electrode provided in Example 1;
[0038] Figure 2 Polarization LSV curves of the hydrogen production electrodes provided for Examples 1-3 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0039] As used herein:
[0040] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0041] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0042] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0043] In these examples, parts and percentages are by mass unless otherwise indicated.
[0044] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0045] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0046] In a first aspect, the present application provides a hydrogen production electrode, comprising a metal substrate and a porous coating disposed on the surface of the metal substrate;
[0047] The porous coating comprises a first metal material and a second metal material;
[0048] The first metal material includes one or more of nickel-based metals, cobalt-based metals, and iron-based metals;
[0049] The second metal material includes a lanthanide nickel-based alloy compound.
[0050] In some embodiments, the lanthanide nickel-based alloy compound includes LaNi5, La2Ni7, La X Pr 1-X Ni5, La X Ce 1-X Ni5, MmNi5 Mm refers to one or more rare earth metal elements.
[0051] It should be noted that La2Ni7 is preferred. Alloys containing more lanthanum (La2Ni7) have higher hydrogen storage capacity. Lanthanum has a stronger tendency to hydrogenate, so the higher the lanthanum content in the alloy, the stronger the hydrogen storage capacity; lanthanum has strong catalytic activity and can reduce the hydrogen evolution potential. The addition of praseodymium and cerium can usually improve the kinetics of the hydrogenation reaction, but the hydrogen storage capacity may be slightly lower than that of pure lanthanum hydride; the addition of praseodymium and cerium will increase the catalytic activity of the second metal and reduce the hydrogen evolution potential.
[0052] In some embodiments, the metal substrate includes one or more of nickel mesh, nickel felt, and nickel foam.
[0053] The second aspect of the present application provides a method for preparing the hydrogen production electrode, comprising:
[0054] The first metal material, the second metal material and the pore-forming agent are first mixed to obtain a coating powder;
[0055] Applying the coating powder to the surface of a metal substrate to obtain a coated substrate;
[0056] The coated substrate and the alkaline solution are mixed for a second time to react to obtain the hydrogen production electrode.
[0057] In some embodiments, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0058] A. The metal substrate is also roughened before coating;
[0059] B. The mass ratio of the first metal material, the second metal material and the pore-forming agent is 60-80:5-10:15-20.
[0060] Optionally, the mass ratio of the first metal material, the second metal material, and the pore-forming agent can be 80:5:15, 75:5:20, 65:5:30, 60:10:30, 75:5:20, or any value between 60-80:5-10:15-30.
[0061] It should be noted that when the mass ratio of the first metal material, the second metal material and the pore-forming agent is 70-80:5-10:15-30, when the mass ratio of the second metal is less than 5, the amount of stored hydrogen is small and the antioxidant effect cannot be achieved, while when the second metal content is too high, the cost is high; when the mass ratio of the pore-forming agent is less than 15, the number of holes created in the catalytic coating is small, the specific surface area is small, the active sites are small, and the catalytic activity is low.
[0062] In some embodiments, the sandblasting pressure for roughening is 0.2 MPa-0.5 MPa, the sandblasting distance is 50 mm-150 mm, and the sandblasting angle is 60°-90°.
[0063] Optionally, the roughening sandblasting pressure can be 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa or any value between 0.2MPa-0.5MPa, the sandblasting distance can be 50mm, 100mm, 150mm or any value between 50mm-150mm, and the sandblasting angle can be 60°, 70°, 80°, 90° or any value between 60°-90°.
[0064] In some embodiments, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0065] A. The coating powder applied during the coating is 240 g / m 2 -300g / m 2 ;
[0066] Optionally, the coating powder applied may be 240 g / m 2 , 250g / m 2 , 260g / m 2 , 270g / m 2 , 280g / m 2 , 290g / m 2 , 300g / m 2 Or 240g / m 2 -300g / m 2 Any value between
[0067] It should be noted that when the powder amount is 240g / m 2 -300g / m 2 When the coating thickness is within the range of 15um-20um, the powder coating amount is less than 240g / m 2 When the coating has few catalytic active sites, the catalytic activity is low; the powder amount is greater than 300g / m 2 When the catalytic activity of the coating increases, it does not increase significantly, but the cost increases rapidly.
[0068] B. The coating includes one or more of plasma spraying, arc spraying, magnetron sputtering, and electroplating.
[0069] In some embodiments, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0070] A. The spraying power of the plasma spraying is 20kW-50kW, the spraying distance is 130mm-170mm, and the spraying angle is 60°-90°;
[0071] Optionally, the spraying power of the plasma spraying can be 20kW, 25kW, 30kW, 35kW or any value between 20kW-35kW, the spraying distance can be 130mm, 140mm, 150mm, 160mm, 170mm or any value between 130mm-170mm, and the spraying angle can be 60°, 70°, 80°, 90° or any value between 60°-90°;
[0072] B. During the plasma spraying process, the argon gas flow rate is 50 L / min-80 L / min, and the hydrogen gas flow rate is 1 L / min-10 L / min.
[0073] Optionally, during plasma spraying, the argon flow rate can be 50 L / min, 60 L / min, 70 L / min, 80 L / min or any value between 50 L / min and 80 L / min, and the hydrogen flow rate can be 1 L / min, 2 L / min, 4 L / min, 6 L / min, 8 L / min, 10 L / min or any value between 1 L / min and 10 L / min.
[0074] In some embodiments, the method for preparing the hydrogen production electrode satisfies at least one of the following conditions:
[0075] A. The reaction temperature is 70°C-90°C and the reaction time is 4h-8h;
[0076] Optionally, the reaction temperature may be 70°C, 80°C, 90°C or any value between 70°C and 90°C, and the reaction time may be 4h, 5h, 6h, 7h, 8h or any value between 4h and 8h;
[0077] B. The alkaline solution includes KOH solution and / or NaOH solution.
[0078] A third aspect of the present application provides a hydrogen production device, comprising the hydrogen production electrode or a hydrogen production electrode prepared by the hydrogen production electrode preparation method.
[0079] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0080] Example 1
[0081] In a first aspect, the present embodiment provides a hydrogen production electrode, comprising a metal substrate and a porous coating disposed on the surface of the metal substrate;
[0082] The metal substrate is a nickel mesh, the porous coating is a first metal material and a second metal material, the first metal material is nickel powder, and the second metal material is La2Ni7.
[0083] A second aspect of this embodiment provides a method for preparing a hydrogen production electrode, the specific steps comprising:
[0084] S1: mixing the first metal material, the second metal material and the pore-forming agent aluminum powder in a mass ratio of 70:10:20 to obtain a coating powder;
[0085] S2: The surface of the metal substrate is roughened by white corundum sandblasting, the sandblasting pressure is 0.3 MPa, the sandblasting distance is 100 mm, and the angle is 60°, and the coating powder is applied to the roughened metal substrate surface by plasma spraying to obtain a coated substrate, wherein the spraying power of the plasma spraying is 35 kW, the spraying distance is 150 mm, the spraying angle is 90°, the argon flow rate is 40 L / min, and the hydrogen flow rate is 5 L / min;
[0086] S3: The coated substrate is immersed in a 30 wt % KOH solution at 80° C. and reacted for 6 h to obtain a hydrogen production electrode.
[0087] The SEM image of the hydrogen production electrode is as follows Figure 1 shown.
[0088] Example 2
[0089] The difference from Example 1 is that the first metal material is Ni 0.9 Mo 0.1 Alloy, the second metal material is La 0.9 Pr 0.1 Ni5, and the mass ratio of the first metal material, the second metal material and the pore-forming agent aluminum powder is 70:10:20.
[0090] Example 3
[0091] The difference from Example 1 is that the second metal material is La 0.8Ce 0.2 Ni5.
[0092] Comparative Example 1
[0093] The difference from Example 1 is that the second metal material is not provided. The mass ratio of Ni to pore-forming agent aluminum powder is 80:20.
[0094] Comparative Example 2
[0095] The difference from Example 1 is that the first metal material is not provided. The mass ratio of La2Ni7 to pore-forming agent aluminum powder is 80:20.
[0096] Comparative Example 3
[0097] The difference from Example 1 is that no pore-forming agent is added during the preparation of the hydrogen production electrode. The mass ratio of the first metal material to the second metal material is 90:10.
[0098] Comparative Example 4
[0099] The difference from Example 1 is that the lanthanide nickel-based alloy compound is replaced by NiCr alloy.
[0100] Comparative Example 5
[0101] The difference from Example 1 is that the mass ratio of the first metal material, the second metal material and the pore-forming agent is 93:2:5.
[0102] The polarization curve LSV test of the above examples 1-3 and comparative examples 1-5 is carried out. The specific results are as follows Figure 2 shown.
[0103] The above embodiments and comparative examples were subjected to overpotential, positive and reverse polarization stability and ultrasonic weight loss rate tests. The specific test results are shown in Table 1.
[0104] Overpotential: In a three-electrode test system, the chronopotentiometry is used to measure the working potential of the test electrode at a certain current density, and the overpotential of the electrode is calculated using the difference between the working potential and the theoretical potential.
[0105] The test electrode is in the shape of a square with a pole ear, the size of the pole ear part is 10mm×5mm, and the effective area of the test part is calculated according to the geometric area, and its size is 20mm×20mm; the reference electrode uses a mercury / mercury oxide electrode; the counter electrode uses a pure platinum electrode with a purity of not less than 99.9%, and an effective size of 20mm×20mm; the test solution temperature is controlled at 80.0℃±2℃. Stir the test solution and keep the magnetic speed at 300r / min.
[0106] The overpotential test method is:
[0107] a) Measure the open circuit potential of the working electrode for at least 30 minutes. When the potential fluctuation is stable within 5mV / min, proceed to the next step of the test.
[0108] b) Turn on the chronopotentiometry measurement function and set the current density to 5000A / m 2 Under this condition, measure the curve of hydrogen evolution electrode potential changing with time. The sampling frequency should be not less than 1 Hz, the test time should be not less than 60 min, and record the potential value of the test electrode. The average potential value between 50 min and 60 min should be used as the working potential under this current density.
[0109] c) Turn on the chronopotentiometry measurement function and set the current density to -100A / m 2 and -1000A / m 2 Under the conditions, measure the curve of hydrogen evolution electrode potential changing with time respectively. The sampling frequency should be not less than 1 Hz, the test time should be not less than 60 min, and record the potential value of the test electrode. The average potential value between 50 min and 60 min should be used as the working potential under the current density.
[0110] Positive and negative polarization stability: Test the performance changes of the hydrogen evolution electrode after cathodic polarization (positive polarization) at a higher current density and anodic polarization (reverse polarization) at a lower current density. In a two-electrode system, the electrode is subjected to positive and negative polarization tests for 1000 cycles; before and after the positive and negative polarization performance tests, the electrode overpotential is tested in a three-electrode system, and the difference in the obtained overpotential is characterized as the positive and negative polarization stability; the solution used is 1.00mol / L±0.05mol / LKOH solution.
[0111] The test method for positive and negative polarization stability is:
[0112] a) In the three-electrode test system, measure the overpotential η of each test electrode before forward and reverse polarization according to the following steps i.0 ;
[0113] ①Measure the open circuit potential of the working electrode for at least 30 minutes. When the potential fluctuation is stable within 5mV / min, the next step of the test can be carried out.
[0114] ② Turn on the chronopotentiometry measurement function and set the current density to 5000A / m 2 Under this condition, measure the curve of hydrogen evolution electrode potential changing with time. The sampling frequency should be not less than 1 Hz, the test time should be not less than 60 min, and record the potential value of the test electrode. The average potential value between 50 min and 60 min should be used as the working potential under this current density.
[0115] ③ Turn on the chronopotentiometry measurement function and set the current density to -5000A / m 2Under the current density, measure the curve of hydrogen evolution electrode potential changing with time. The sampling frequency should be not less than 1 Hz, the test time should be not less than 60 min, and record the potential value of the test electrode. The average potential value between 50 min and 60 min should be used as the working potential under the current density.
[0116] b) In the two-electrode test system, start the current step method test, and each test electrode is subjected to 5000A / m in a single cycle. 2 After 10 min of positive polarization, the current was reversed to 300 A / m 2 Reverse polarization was performed for 10 min under the condition of 10°C and the cycle was repeated 1000 times.
[0117] c) After the test electrode has undergone positive and negative polarization tests, measure the overpotential η of each test electrode according to the method specified in a). i.1000 .
[0118]
[0119] Ultrasonic weight loss rate test: Place the test electrode in the ultrasonic weight loss test system, perform ultrasonic oscillation treatment for a period of time at a certain frequency and power, measure the mass of the electrode before and after ultrasonic oscillation, and calculate the ultrasonic weight loss.
[0120] The ultrasonic frequency is 40kHz, the ultrasonic power is 300W, the electrode size is a 40mm×40mm rectangle; a set of test electrodes has 3 pieces, and the 3 pieces are from the same batch of electrodes; the temperature of the test liquid is 40℃±1℃.
[0121] The specific test method for ultrasonic weight loss rate is:
[0122] a) Treatment: Rinse the electrode repeatedly with pure water for at least 3 times, and then rinse the electrode repeatedly with anhydrous ethanol for at least 3 times; and dry the electrode in a vacuum oven at 70°C and a vacuum degree of no more than 200Pa for more than 2 hours.
[0123] b) Weighing: Weigh the three electrodes in turn and record their initial mass M0 with an accuracy of 0.1 mg.
[0124] c) Ultrasonic treatment: treat one electrode each time, place the electrode horizontally at the bottom of a 250mL glass beaker containing 200mL of test solution, place the beaker in the middle of the ultrasonic cleaning machine and fix it, add water to the ultrasonic cleaning machine until the water level in the inner tank is 50mm, and then treat continuously for 120min at a temperature of 40℃±1℃.
[0125] d) Take out the test electrodes and process and weigh the post-ultrasonication electrodes according to the steps in a) and b), and record the final mass M1 of the three electrodes respectively.
[0126]
[0127] Table 1 Performance test
[0128]
[0129] analyze:
[0130] As shown in Table 1, the electrode of Example 1 has low overpotential and excellent electrochemical activity, high forward and reverse polarization stability, and good coating bonding; the electrode of Example 2 is doped with Mo, and its overpotential is the lowest, and the forward and reverse polarization stability is slightly lower than that of Example 1; the second metal of Example 3 is doped with rare earth Ce, and its forward and reverse polarization stability is lower than that of Example 1; Comparative Example 1 does not add the second metal material, and its forward and reverse polarization stability is the worst; Comparative Example 2 does not add the first metal material (electrochemical catalytic active component), and its overpotential is the highest, and the forward and reverse polarization stability is the best; Comparative Example 3 does not add a pore-forming agent, and its specific surface area is small, the number of active sites is small, the electrochemical activity is low, and the overpotential is high; Comparative Example 4 replaces the second metal lanthanide nickel-based alloy compound with NiCr alloy. Since no hydrogen storage material is added, the surface is easily oxidized during forward and reverse polarization, and the stability is the worst; Comparative Example 5, the mass ratio of the first metal material, the second metal material, and the pore-forming agent is 93:2:5, which is not within the appropriate ratio range. It has low catalytic activity, high overpotential, and poor forward and reverse polarization stability.
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0132] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A hydrogen production electrode, characterized in that: It comprises a metal substrate and a porous coating arranged on the surface of the metal substrate; The porous coating comprises a first metal material and a second metal material; The first metal material includes one or more of nickel-based metals, cobalt-based metals, and iron-based metals; The second metal material includes a lanthanide nickel-based alloy compound.
2. The hydrogen production electrode according to claim 1, characterized in that: The lanthanide nickel-based alloy compounds include LaNi5, La2Ni7, La X Pr 1-X Ni5, La X Ce 1-X One or more of Ni5, MmNi5.
3. The hydrogen production electrode according to claim 1, characterized in that: The metal matrix includes one or more of nickel mesh, nickel felt, and nickel foam.
4. A method for preparing a hydrogen production electrode according to any one of claims 1 to 3, characterized in that: include: The first metal material, the second metal material and the pore-forming agent are first mixed to obtain a coating powder; Applying the coating powder to the surface of a metal substrate to obtain a coated substrate; The coated substrate is immersed in an alkaline solution for activation, and the hydrogen production electrode is obtained by reaction.
5. The method for preparing a hydrogen production electrode according to claim 4, characterized in that: At least one of the following conditions is met: A. The metal substrate is also roughened before coating; B. The mass ratio of the first metal material, the second metal material and the pore-forming agent is 60-80:5-10:15-30.
6. The method for preparing a hydrogen production electrode according to claim 5, characterized in that: The sandblasting pressure for the roughening is 0.2MPa-0.5MPa, the sandblasting distance is 50mm-150mm, and the sandblasting angle is 60°-90°.
7. The method for preparing a hydrogen production electrode according to claim 4, characterized in that: At least one of the following conditions is met: A. The coating powder applied during the coating is 240 g / m 2 -300g / m 2 ; B. The coating includes one or more of plasma spraying, arc spraying, magnetron sputtering, and electroplating.
8. The method for preparing a hydrogen production electrode according to claim 7, characterized in that: At least one of the following conditions is met: A. The spraying power of the plasma spraying is 20kW-50kW, the spraying distance is 130mm-170mm, and the spraying angle is 60°-90°; B. During the plasma spraying process, the argon flow rate is 50L / min-80L / min, and the hydrogen flow rate is 1L / min-10L / min.
9. The method for preparing a hydrogen production electrode according to any one of claims 4 to 8, characterized in that: At least one of the following conditions is met: A. The reaction temperature is 70°C-90°C and the reaction time is 4h-8h; B. The alkaline solution includes KOH solution and / or NaOH solution.
10. A hydrogen production device, characterized in that: The hydrogen production electrode comprises the hydrogen production electrode according to any one of claims 1 to 4 or is prepared by the method for preparing the hydrogen production electrode according to any one of claims 5 to 9.
Citation Information
Cited By
Electrode catalyst, catalyst electrode and preparation method thereof
CN121344644A